2020
DOI: 10.48550/arxiv.2002.12119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tree Polymatrix Games are PPAD-hard

Argyrios Deligkas,
John Fearnley,
Rahul Savani

Abstract: We prove that it is PPAD-hard to compute a Nash equilibrium in a tree polymatrix game with twenty actions per player. This is the first PPAD hardness result for a game with a constant number of actions per player where the interaction graph is acyclic. Along the way we show PPAD-hardness for finding an -fixed point of a 2D-LinearFIXP instance, when is any constant less than ( √ 2 − 1)/2 ≈ 0.2071. This lifts the hardness regime from polynomially small approximations in k-dimensions to constant approximations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, multi-player polymatrix games [52] can also be equivalently transformed to bilinear games [46]. Generally speaking, the existing literature mainly focuses on the computational complexity and polynomial-time algorithm design for approximating NE of bilinear games [53], bimatrix games [54], polymatrix games [55], and the Colonel Blotto game [56]. Recently, it is shown that NE computation in two-player nonzero-sum games with rank ≥ 2 is PPAD-hard [57], [58].…”
Section: A Zero-sum Games (Zsgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, multi-player polymatrix games [52] can also be equivalently transformed to bilinear games [46]. Generally speaking, the existing literature mainly focuses on the computational complexity and polynomial-time algorithm design for approximating NE of bilinear games [53], bimatrix games [54], polymatrix games [55], and the Colonel Blotto game [56]. Recently, it is shown that NE computation in two-player nonzero-sum games with rank ≥ 2 is PPAD-hard [57], [58].…”
Section: A Zero-sum Games (Zsgs)mentioning
confidence: 99%
“…And computing a 1/n c s -approximate NE is PPAD-hard even for imitation games for any c > 0 [50], where n s is the number of moves available to the players, and a polynomial-time algorithm was developed for finding an approximate NE in [50]. Also, computing an NE in a tree polymatrix game with twenty actions per player is PPAD-hard [55], and a polynomial-time algorithm for 1/3-approximate NE in bimatrix games was proposed in [54], which is the state-of-the-art in the literature. For the Colonel Blotto game, efficient and simple algorithms have been recently provided in [59]- [61], and meanwhile, various scenarios have been extended for this game, including dynamic Colonel Blotto game [62], generalized Colonel Blotto and generalized lottery Blotto games [63], and multiplayer cases [61], [64].…”
Section: A Zero-sum Games (Zsgs)mentioning
confidence: 99%